Of family, futures and fear in a Balinese ward: Some preliminary thoughts toward a new project - Richard Fox (Universitas Udayana, 2017)
The link between family, fear and women’s bodies has a complicated history in Indonesia, tied to both international aid and economic development—as well as, in more recent years, to consumerism and transnational capital. Yet, if the ‘small happy and prosperous family norm’ is now the aspiration of many young Balinese, this was not always the case. Today advertisements for family planning technology encourage women to overcome fears of discomfort and physical side-effects in order to realize ‘the family of their dreams’. But the fears of earlier days were not so easily allayed—incited by stories of infertility, infection and death resulting from use of the IUD. What do older Balinese remember of the early days of the KB program? How does this compare with the aspirations of younger Balinese as they pursue the pleasures of life in a ‘small family’ and experience its anxieties? This article presents preliminary reflections on a new project exploring how Balinese differing in gender, generation and social class talk about and act on their plans for the future. Given its importance for both state bureaucratic and commercial representations of domestic life, the ideal of the patriarchal nuclear family figures centrally in these reflections.